Des inégalités d’appropriation des enjeux énergétiques territoriaux? Analyse sociologique d’un instrument coopératif autour de l’éolien « citoyen » - Guillaume Christen; Philippe Hamman (VertigO)
How can social actors concretely contribute to the production of “green energy” as a common good? This article analyses the differentiated relations inhabitants have in local territories regarding participatory instruments that can implement the energy transition. The study is based on a sociological survey conducted since 2012, dealing with a significant example in a rural area in Alsace (France). This case allows the authors to consider the implementation of a popular shareholding instrument concerning a “citizen” wind project. Even if this incentive instrument promotes the reconciliation of the inhabitants and the wind technology, its operationalization could not avoid encountering social inequities in participation as well as in the local appropriation of the plan, especially because the organizational processes of the wind energy are built on specific expert knowledge. These disparities are not strictly related to unequal exposures of the actors regarding environmental risks (pollutions, annoyances); they are also disparities of knowledge between the different involved actors, and unequal capacities for participation and mobilization around environmental projects.